Unlocking the Secrets of Cebulactam A1: Predictive Insights into Binding with Fall Armyworm Spodoptera frugiferda’s Arylalkylamine N-Acyltransferase - Alcantara, Edwin P. (Jurnal Perlindungan Tanaman Indonesia, 2025)
The necessity for an insecticide with a novel mode of action to enhance existing approaches for managing the fall armyworm (FAW), Spodoptera frugiperda, is evident. This study aimed to predict the binding of cebulactam A1 to the FAW’s arylalkylamine N-acyltransferase (aaNAT). A molecular docking approach was employed to estimate the binding affinity of cebulactam A1 to FAW aaNAT. The docking results were validated through molecular dynamics simulation and molecular mechanics Poisson-Boltzmann Surface Area (MM-PBSA) analysis. Subsequently, a per-residue energy decomposition analysis was conducted to identify specific amino acid residues involved in ligand binding. The binding affinity and inhibition constant (Ki) predicted from molecular docking were -8.1 kcal/mol and 1.16 µM, respectively. The binding stability was confirmed for 350 ns through molecular dynamics simulation. The predicted free energy of binding (ΔGbind) of cebulactam A1 to the target receptor was -7.18 kcal/mol. The per-residue energy decomposition analysis identified Ser93, Phe109, and Tyr113 as key residues likely involved in the molecular recognition of cebulactam A1 at the FAW receptor binding site. Collectively, these findings suggest that cebulactam A1 is a promising candidate for development as an inhibitor of the FAW aaNAT enzyme.